Ti5Si3 / ZrB2 composite material and hot pressing sintering method thereof
The preparation of Ti5Si3/ZrB2 composite material through hot press sintering process solves the problems of high preparation efficiency and cost in the prior art, realizes the preparation of materials with high density and good performance, and promotes its wide application in the engineering field.
Patent Information
- Application Number
- CN202411448646.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
AI Technical Summary
In the prior art, when preparing Ti5Si3/ZrB2 composite materials, the liquid metal impregnation method is complex and costly, and it is difficult to prepare dense materials with normal pressure sintering, the discharge plasma sintering cost is high, and the thermal isostatic sintering equipment is expensive, resulting in preparation efficiency and cost. question.
Using the hot press sintering process, the mixture of Ti5Si3 intermetallic compound powder and ZrB2 powder was prepared by mechanical alloying and heat treatment. Al2O3 and Y2O3 powder were added as sintering aids, and dense Ti5Si3/ZrB2 composite material was formed by wet bulb milling and hot press sintering. .
The rapid molding of low-cost and simplified process was achieved, and the Ti5Si3/ZrB2 composite material with high density and uniform microstructure was prepared, with high mechanical properties and good wear resistance and high temperature oxidation resistance.
Smart Images

Figure CN119320890A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a Ti5Si3 / ZrB2 composite material and a hot pressing sintering method thereof. Background Art
[0002] Titanium-silicon (Ti-Si) intermetallic compounds mainly include Ti5Si3 intermetallic compounds. Ti5Si3 intermetallic compounds have high melting point (2130°C), low density (4.65g / cm 3 ) and excellent high-temperature properties such as high high-temperature hardness, good high-temperature stability, and oxidation resistance, and it is expected to be used in high-temperature structural materials above 1300℃. The melting point of Ti5Si3 intermetallic compounds is close to or even higher than that of high-temperature structural ceramics, but the density is much lower than some high-temperature structural ceramics and high-temperature alloys, which is equivalent to titanium alloys, and has the potential to be used at high temperatures. In addition, due to its low electrical resistance and thermal resistance, Ti5Si3 intermetallic compounds are also expected to be used in electrical connection structures and diffusion barriers. Ti5Si3 is an intermetallic compound with excellent performance, and its performance characteristics are mainly reflected in high hardness, good wear resistance and certain fracture toughness. Ti5Si3 intermetallic compounds have high hardness, which makes it excellent in wear resistance. The TiCo / Ti5Si3 dual-phase intermetallic compound alloy prepared by laser melting technology, with metal silicide Ti5Si3 as the wear-resistant reinforcement phase, shows excellent room temperature dry sliding wear resistance. With the increase of TiCo content, although the volume fraction of the primary phase Ti5Si3 and the microhardness of the alloy decrease, the toughness and wear resistance of the alloy are significantly improved. This shows that the high hardness of Ti5Si3 and the high toughness of TiCo work together to give the alloy excellent wear resistance. Due to the excellent performance of Ti5Si3, it has a wide range of applications in many fields. Ti5Si3 has a wide range of application potential in many fields with its high hardness, good wear resistance and optimization of alloying principle behavior. Ti5Si3 is an intermetallic compound with high melting point and high specific strength. Its crystal structure belongs to a complex hexagonal structure and has the potential to be used at high temperature (1600℃). Microstructural analysis of Ti5Si3 shows that it has excellent physical properties such as high melting point and low density. Its melting point is comparable to that of ceramics, while its density is lower than that of ceramics and high-temperature alloys, and is close to that of titanium alloys, which gives it unique advantages in some applications. However, Ti5Si3 has a large room temperature brittleness, which limits its application range to a certain extent, but its performance can be improved and its application field can be broadened through alloying and other means. The melting point of Ti5Si3 is as high as 2130℃ and its density is 4.65g / cm 3, these characteristics make it have excellent stability in high temperature environment while maintaining a light weight, which has potential application value in aviation, aerospace and other fields. Although Ti5Si3 performs well at high temperatures, its brittleness is still large at room temperature, which limits its use in aviation and aerospace applications. Through alloying, heat treatment and other methods, its room temperature brittleness can be improved to a certain extent, and its toughness and strength at room temperature can be improved. The performance of Ti5Si3 can be effectively improved by adding appropriate amounts of alloying elements such as Nb and Cr. Appropriate amounts of Nb and Cr can weaken the thermal expansion anisotropy of Ti5Si3, improve its toughness and hardness, and thus broaden its application range. As a high-performance intermetallic compound, Ti5Si3 can significantly improve its performance under different temperatures and environments through proper alloying and heat treatment, providing new material solutions for various industrial and scientific fields.
[0003] Zirconium diboride (ZrB2) is an ultra-high temperature ceramic material that is valued for its outstanding physical and chemical properties. The molecular formula of zirconium diboride is ZrB2, where each zirconium atom is combined with two boron atoms to form a dense hexagonal structure, which gives the material a high degree of stability and excellent physical properties. Zirconium diboride has a high melting point (about 3246°C), can maintain structural stability in extremely high temperature environments, and shows excellent corrosion resistance, low oxidation rate and good electrical conductivity. In addition, the thermal conductivity and thermal shock stability of zirconium diboride are extremely critical for the manufacture of target materials. Zirconium diboride has a molecular weight of about 6.09 g / cm 3Its high density and hardness of about 25GPa make it excellent in wear and scratch resistance, suitable for industrial knives and protective coating applications. Although zirconium diboride behaves as an electrical insulator at room temperature, its electrical conductivity increases at high temperatures, showing semiconductor behavior, which makes it possible to use it in high-temperature electronic devices. It also has a relatively high thermal conductivity, which is at a good level among ceramic materials, and is suitable for use in thermal management systems such as heat sinks and heat exchangers. Zirconium diboride has a low coefficient of thermal expansion, which means that its volume and shape change less when the temperature changes, especially in applications with high dimensional stability requirements. In addition, under certain conditions, zirconium diboride can exhibit semiconductor behavior, which makes it possible to develop new high-temperature semiconductor devices. Zirconium diboride plays an indispensable role in many high-tech fields due to its unique physical, chemical, mechanical, thermal and electrical properties, and has cross-domain applications in many fields from aerospace to semiconductors. Zirconium diboride ceramics are valued and applied in the fields of high-temperature structural ceramic materials, composite materials, refractory materials, electrode materials, and nuclear control materials because of their high melting point and hardness, good electrical and thermal conductivity, and strong neutron control ability. Such as turbine blades in the aviation industry, magnetohydrodynamic generator motors, etc. In addition, compared with many ceramic materials, it has better electrical conductivity and can be used to produce parts with complex shapes using wire cutting technology. ZrB2 ceramics are excellent special refractory materials and can be used as high-temperature thermocouple protection sleeves, casting molds, crucibles for metallurgical metals, etc. ZrB2 is suitable for electric shock materials and electrode materials due to its low resistivity and electronic conduction mechanism. It can be used in electrodes of metal thermocouples and high-temperature heating elements. Due to its extremely high hardness, ZrB2 is a good wear-resistant material and has good applications in cutting tools and cutting tools. ZrB2 has good corrosion resistance, and the corrosion resistance and oxidation resistance of ZrB2 have been studied in depth. Zirconium diboride (ZrB2) is a high-temperature material with a high melting point and hardness. Its melting point is 3246℃, and it is a very stable compound. Zirconium diboride has excellent mechanical properties, high temperature resistance, chemical stability and electrical conductivity, so it is widely used in aviation, aerospace, energy, automobiles and ceramics. Although the price of zirconium diboride is relatively high, its performance is far better than other materials, so it has been widely used in high-end technology fields.
[0004] Ti5Si3 intermetallic compounds have high strength, high toughness, high melting point, high hardness, good wear resistance, corrosion resistance and high temperature oxidation resistance and are widely used in the engineering field. Moreover, the mechanical properties of Ti5Si3 intermetallic compounds are relatively high, and they can be used as reinforcing and toughening phases of ceramic materials to improve the mechanical properties and high temperature oxidation resistance of ceramic materials. Zirconium diboride ceramic materials have high strength and high hardness, good wear resistance and high temperature oxidation resistance, and are widely used in the engineering field. However, zirconium diboride ceramics are relatively brittle and have low fracture toughness, so it is necessary to add reinforcing and toughening phases to the ZrB2 matrix. Ti5Si3 intermetallic compounds have good compatibility with ZrB2, and Ti5Si3 intermetallic compounds can be added to the ZrB2 matrix to form Ti5Si3 / ZrB2 composite materials through compounding, which will greatly improve and enhance the mechanical properties of ZrB2 ceramic materials. Ti5Si3 / ZrB2 composite materials have the high strength, high toughness, high hardness and high wear resistance of Ti5Si3 intermetallic compounds, and also have the high hardness and high wear resistance of ZrB2 ceramics. Ti5Si3 / ZrB2 composite materials will have excellent performance. Ti5Si3 / ZrB2 composite materials have high mechanical properties, high hardness and wear resistance, high high temperature oxidation resistance and corrosion resistance. Therefore, the preparation of Ti5Si3 / ZrB2 composite materials has become the main research focus and hotspot. For the preparation process of intermetallic compound / ceramic matrix composite materials, some researchers use liquid metal infiltration method to prepare intermetallic compound / ceramic matrix composite materials. Due to the high melting point of Ti5Si3 intermetallic compound, the melting point of Ti5Si3 intermetallic compound is 2130℃, and it is difficult to form a liquid phase at a very high temperature. In addition, Ti5Si3 intermetallic compounds and ZrB2 ceramics have poor wettability and other problems. Ti5Si3 intermetallic compounds are difficult to penetrate into ZrB2 ceramic preforms, so it is impossible to use liquid metal infiltration method to prepare Ti5Si3 / ZrB2 composite materials. Therefore, Ti5Si3 / ZrB2 composite materials can only be prepared by powder metallurgy process. Powder metallurgy process mainly includes normal pressure sintering process, hot pressing sintering process, spark plasma sintering process, hot isostatic pressing sintering process. Normal pressure sintering process, that is, pressureless sintering process, cannot prepare dense Ti5Si3 / ZrB2 composite materials because there is no pressure for sintering. What is finally obtained is only a Ti5Si3 / ZrB2 composite material sintered block with extremely high porosity, and it is impossible to obtain a dense sintered block. Therefore, the mechanical properties of the obtained composite material are poor and cannot be applied to the engineering field. Therefore, it cannot be prepared by normal pressure sintering process.Although the spark plasma sintering process can produce dense Ti5Si3 / ZrB2 composite materials, the preparation process of the spark plasma sintering process is very complicated, the sintering time is relatively short, the sintered sample cannot reach complete density, the sintering cost is high, the spark plasma sintering equipment is very expensive, and the preparation cost is too high, so the spark plasma sintering process cannot be used for preparation. The hot isostatic pressing sintering process requires a hot isostatic press, the hot isostatic press equipment is expensive, the sintering cost is too high, and the preparation process is very complicated, so the hot isostatic pressing sintering process cannot be used for preparation. Therefore, the hot pressing sintering process with relatively low sintering cost can only be used to prepare Ti5Si3 / ZrB2 composite materials. The hot pressing sintering process can prepare a Ti5Si3 / ZrB2 composite material sintered block with high density, and the Ti5Si3 / ZrB2 composite material sintered block prepared by the hot pressing sintering process has high mechanical properties, high density, uniform and dense microstructure, excellent wear resistance, excellent corrosion resistance and excellent high temperature oxidation resistance. Therefore, the hot pressing sintering process is the most suitable sintering process for preparing Ti5Si3 / ZrB2 composite materials. The hot pressing sintering process has the advantages of fast sintering speed, high density of sintered products, and can achieve mass production. The hot pressing sintering process uses resistance heating to heat the raw material powder in the mold, and applies axial pressure to the raw material powder in the mold, and keeps the temperature and pressure for a certain period of time to obtain a dense sintered product. In order to achieve rapid molding and sintering of composite materials, the present invention proposes to prepare Ti5Si3 / ZrB2 composite materials using hot pressing sintering process. Summary of the invention
[0005] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a Ti5Si3 / ZrB2 composite material and a hot pressing sintering method thereof. The present invention overcomes the problems that the traditional liquid metal infiltration process is too complicated in operation, the preparation cost is high, and the shape and size of the prepared product are limited; the present invention also overcomes the disadvantage that it is difficult to prepare a high-density composite material by using a normal pressure sintering process, the present invention also overcomes the problems that the preparation cost is high by using a spark plasma sintering process, the spark plasma sintering equipment is expensive, and the present invention also overcomes the problems that the sintering cost is too high by using a hot isostatic pressing sintering process, the hot isostatic pressing sintering equipment is expensive, and the sintering process is too complicated. The present invention adopts a hot pressing sintering process, which simplifies the production process and reduces the production cost. At the same time, it can also produce sintered products with complex shapes. The prepared Ti5Si3 / ZrB2 composite material has the characteristics of high density and high mechanical properties.
[0006] The present invention proposes to prepare Ti5Si3 / ZrB2 composite material blocks by using a hot pressing sintering process. The hot pressing sintering process has the following process steps: first, the prepared Ti5Si3 / ZrB2 composite powder is loaded into a graphite mold, and then placed in a hot pressing sintering furnace. The sintered blank is subjected to high temperature and high heat by resistance heating, and a certain axial pressure is applied, and the heat preservation and pressure are maintained for a certain period of time for sintering. The hot pressing sintering process is used to sinter the blank to form a composite material product. The hot pressing sintering process has low cost and a simple preparation process. It can realize rapid molding and sintering to form a composite material product. It is suitable for industrial production and is conducive to industrialization. Therefore, the present invention proposes to prepare Ti5Si3 / ZrB2 composite material blocks by using a hot pressing sintering process. First, a mechanical alloying process and a heat treatment process are used to prepare Ti5Si3 intermetallic compound powder, and the Ti5Si3 intermetallic compound powder is mixed with ZrB2 powder, and 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids are added, and 10 parts by mass of fine silicon powder are added as sintering aids, and Ti5Si3 / ZrB2 composite powder is prepared by wet ball milling and drying, and the prepared Ti5Si3 / ZrB2 composite powder is loaded into a graphite mold, and a Ti5Si3 / ZrB2 composite material block is prepared by a hot pressing sintering process. The method adopted by the present invention is to utilize the advantages of the hot pressing sintering process with rapid prototyping, so that the Ti5Si3 intermetallic compound particles and the ZrB2 particles can be sintered into a dense Ti5Si3 / ZrB2 composite material block under the action of heating and pressurizing sintering, so the Ti5Si3 / ZrB2 composite material block is prepared by a hot pressing sintering process.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A Ti5Si3 / ZrB2 composite material, comprising the following components by weight:
[0009] 10 to 70 parts of Ti5Si3 intermetallic compound powder, with Ti5Si3 intermetallic compound as a strengthening and toughening phase;
[0010] 30 to 90 parts of ZrB2 powder, with ZrB2 as the matrix;
[0011] 10 parts of Al2O3 powder and Y2O3 powder as sintering aids;
[0012] 10 parts of fine silicon powder as sintering aid.
[0013] The Ti5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, wherein the Ti-Si intermetallic compound powder is prepared by ball milling for 80 hours using the mechanical alloying process; the prepared Ti-Si intermetallic compound powder is subjected to a heat treatment process, wherein the heat treatment process is performed at a heat treatment temperature of 1000°C to 1400°C, the insulation time is 1 hour, and the heat treatment process is performed under vacuum conditions, and the Ti5Si3 intermetallic compound powder is prepared by the heat treatment process.
[0014] The molar ratio of Ti:Si in the Ti5Si3 intermetallic compound powder is 63:37.
[0015] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0016] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0017] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0018] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0019] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and the mixture is mixed by mechanical ball milling for 24 hours, and a slurry is prepared by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and the strip sample is pressed into a strip sample with a size of 50 mm×5 mm×6 mm by a pressure molding machine at a pressure of 100 MPa to 200 MPa for a holding time of 3 minutes. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1000°C to 1400°C, and the holding time is 1 hour; at a vacuum degree of 10-2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0020] Step 3: 10 to 70 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 are mixed with 30 to 90 parts of ZrB2 powder to obtain a composite powder, 3 to 9 parts by weight of Al2O3 powder and 1 to 7 parts by weight of Y2O3 powder are added to the composite powder as sintering aids, and 10 parts by weight of fine silicon powder is added as a sintering aid to obtain a mixed powder A composed of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; the mixed powder is The powder A is subjected to a wet ball milling mixing process by mechanical ball milling, the mixed powder A is loaded into a ball milling jar, 100 to 400 ml of anhydrous ethanol and 30 to 60 agate grinding balls with a diameter of 10 to 16 mm are added to the ball milling jar for mechanical ball milling mixing for 24 hours to prepare a slurry; the slurry is loaded into a glass beaker and then placed in an oven for drying at 100° C. for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 10 to 70 parts;
[0021] Step 4: Mix the Ti5Si3 / ZrB2 composite powder obtained in step 3 with 10 parts of phenolic resin binder and put them into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to make a slurry. The slurry is put into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder B containing a phenolic resin binder; the mixed powder B is put into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 100MPa to 200MPa for 3 minutes. The method comprises the following steps: pressing the sample into a disc with a diameter of 40 mm and a height of about 10 mm; putting the disc into a latex glove, wrapping it with the latex glove, sealing it and putting it into a cold isostatic press, wherein the medium in the cold isostatic press is hydraulic oil, and the pressure in the cold isostatic press is 100 MPa to 200 MPa for a holding time of 5 minutes. After the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense Ti5Si3 / ZrB2 composite powder preform, thereby obtaining a disc with a diameter of 40 mm and a height of 8 mm; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0022] Step 5: Place the Ti5Si3 / ZrB2 composite powder preform prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering; the vacuum hot pressing sintering process preparation method is: sintering temperature is 1500℃~1800℃, hot pressing pressure is 35MPa, holding time is 2h, vacuum degree is 10 -2 Pa, the heating rate is 10-35℃ / min; after vacuum hot pressing sintering, it is cooled with the furnace to prepare Ti5Si3 / ZrB2 composite material. The Ti5Si3 / ZrB2 composite material obtained by hot pressing sintering process is a sintered disc sample with a diameter of 40mm and a height of 6mm, that is, a sintered block of Ti5Si3 / ZrB2 composite material; the mass fraction of Ti5Si3 intermetallic compound in Ti5Si3 / ZrB2 composite material is 10-70 parts; a small amount of phenolic resin is completely decomposed and volatilized during high temperature hot pressing sintering, and there is no residual phenolic resin in the obtained sintered block.
[0023] In the step 1, the average particle size of the Ti-Si intermetallic compound powder prepared by ball milling for 60 hours using a mechanical alloying process is 10 to 15 μm, and the powder particle size is extremely fine. The particle size of the Ti5Si3 intermetallic compound powder obtained after the heat treatment process is still 10 to 15 μm, and the obtained Ti5Si3 intermetallic compound powder has an ordered structure.
[0024] In the step three, the particle size of the ZrB2 powder is 3 to 5 μm, and the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 10 to 70 parts.
[0025] The beneficial effects of the present invention are:
[0026] For the preparation process of intermetallic compound / ceramic matrix composite materials, some researchers use liquid metal infiltration method to prepare intermetallic compound / ceramic matrix composite materials. Due to the high melting point of Ti5Si3 intermetallic compound, the melting point of Ti5Si3 intermetallic compound is 2130℃, and it is difficult to form a liquid phase at a very high temperature. In addition, there are problems such as poor wettability between Ti5Si3 intermetallic compound and ZrB2 ceramic. It is difficult for Ti5Si3 intermetallic compound to penetrate into ZrB2 ceramic preform, so it is impossible to use liquid metal infiltration method to prepare Ti5Si3 / ZrB2 composite materials. Therefore, Ti5Si3 / ZrB2 composite materials can only be prepared by powder metallurgy process. The traditional liquid metal melt infiltration process has high cost, complex preparation process, and limited shape and size of the prepared products, making it difficult to achieve large-scale production and industrialization. For Ti5Si3 / ZrB2 composite materials, powder metallurgy process can only be used. Powder metallurgy processes mainly include pressureless sintering, hot pressing, spark plasma sintering, and hot isostatic pressing. The pressureless sintering process is also called pressureless sintering. It is impossible to prepare dense Ti5Si3 / ZrB2 composite materials because there is no pressure for sintering. What is finally obtained is only a sintered block of Ti5Si3 / ZrB2 composite materials with extremely high porosity. It is impossible to obtain a dense sintered block. Therefore, the mechanical properties of the composite materials obtained are poor and cannot be applied to the engineering field. Therefore, the pressureless sintering process cannot be used for preparation. Although the spark plasma sintering process can prepare dense Ti5Si3 / ZrB2 composite materials, the preparation process of the spark plasma sintering process is very complicated, the sintering time is relatively short, the sintered sample cannot reach complete density, the sintering cost is high, the spark plasma sintering equipment is very expensive, and the preparation cost is too high, so the spark plasma sintering process cannot be used for preparation. The hot isostatic pressing sintering process requires a hot isostatic press, and the hot isostatic pressing equipment is expensive, the sintering cost is too high, and the preparation process is very complicated, so the hot isostatic pressing sintering process cannot be used for preparation. Therefore, the hot pressing sintering process with relatively low sintering cost can only be used to prepare the Ti5Si3 / ZrB2 composite material. The present invention adopts mechanical alloying and heat treatment process to prepare Ti5Si3 intermetallic compound powder, and the prepared Ti5Si3 intermetallic compound powder is mixed with ZrB2 powder and 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids are added, and 10 parts by mass of fine silicon powder are added as sintering aids to prepare Ti5Si3 / ZrB2 composite powder by wet ball milling mixing and drying, and prepare Ti5Si3 / ZrB2 composite material block by hot pressing sintering process. The hot pressing sintering process can realize rapid molding, low sintering cost, simple preparation process, can produce sintered products with complex shapes, easy to industrialize, and conducive to industrialization.The hot pressing sintering process is to heat the raw material powder by resistance heating, and at the same time, axial pressure is applied to the raw material powder and the heat and pressure are kept for a certain period of time to realize the sintering product forming. At the same time, in the sintering process of Ti5Si3 / ZrB2 composite material, the hot pressing sintering temperature is 1500℃~1800℃, the hot pressing pressure is 35MPa, the heat preservation time is 2h, and the Ti5Si3 alloy particles and ZrB2 particles are bonded together to form a dense sintered block. The role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O. 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, increases the relative density of the ceramic composite and improves the mechanical properties of the ceramic composite. The role of adding 10 parts by mass of fine silicon powder sintering aid is that the fine silicon powder sintering aid forms liquid silicon liquid at high temperature during the sintering process. The melting point of silicon powder is 1410℃. The liquid silicon liquid formed at high temperature promotes the densification of the ceramic composite matrix, fills the pores, increases the relative density of the ceramic composite and improves the mechanical properties of the ceramic composite. The hot pressing sintering process can obtain a sintered product with high density and uniform and dense microstructure, and the sintered product also has high mechanical properties. The Ti5Si3 / ZrB2 composite material prepared by the hot pressing sintering process has high mechanical properties, good wear resistance, high temperature oxidation resistance and other excellent properties. Therefore, the Ti5Si3 / ZrB2 composite material block prepared by the hot pressing sintering process in the present invention has the advantages of low preparation cost and high performance, can achieve rapid prototyping, and can also prepare parts with complex shapes according to engineering needs, so the present invention has important significance and practical value.
[0027] The hot pressing sintering process is to heat, pressurize and sinter and keep warm for a certain period of time to prepare a dense sintered block. The hot pressing sintering process has the advantages of fast sintering speed, high density of sintered samples and rapid molding. The hot pressing sintering process is a sintering method that fills dry powder into the model and then presses and heats from a uniaxial direction to complete molding and sintering at the same time. Characteristics of the hot pressing sintering process: Since the hot pressing sintering process is heated and pressurized at the same time, the powder is in a thermoplastic state, which is conducive to the contact, diffusion and flow of particles and the mass transfer process, so the molding pressure is small; it can also reduce the sintering temperature and shorten the sintering time to resist the growth of grains and obtain products with fine grains, high density, high mechanical properties and high mechanical properties. Ultra-high purity ceramic products can be produced without adding sintering aids or molding aids. The disadvantages of the hot pressing sintering process are that the hot pressing sintering process is relatively complicated, the hot pressing sintering equipment is relatively complicated, and the mold material requirements are relatively high. Various sintered products can be prepared by the hot pressing sintering process. Hot pressing sintering equipment requires a dedicated hot pressing sintering furnace. The commonly used hot pressing sintering furnace is mainly composed of a heating furnace, a pressurizing device, a mold and a temperature and pressure measuring device. According to the properties of the material, a reducing atmosphere or an inert atmosphere is required. The mold requires high strength and high temperature resistance. High-strength sintered bodies can also be obtained through hot pressing sintering. The hot pressing sintering process can prepare sintered products with higher density and higher mechanical properties. The hot pressing sintering process is to prepare dense sintered samples by heating and pressurizing sintering. Dense sintered products can be prepared through the hot pressing sintering process, and the prepared sintered products have uniform and dense microstructures and higher mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention discloses an X-ray diffraction spectrum of a Ti5Si3 / ZrB2 composite material block prepared by a hot pressing sintering process according to the method provided by the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0030] Example 1
[0031] A Ti5Si3 / ZrB2 composite material, comprising the following components by weight:
[0032] 10 parts of Ti5Si3 intermetallic compound powder, with Ti5Si3 intermetallic compound as the strengthening and toughening phase;
[0033] 90 parts of ZrB2 powder, with ZrB2 as the matrix; 10 parts of Al2O3 powder and Y2O3 powder as sintering aids; 10 parts of fine silicon powder as a sintering aid.
[0034] The Ti5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Ti-Si intermetallic compound powder is prepared by ball milling for 80 hours using the mechanical alloying process; the prepared Ti-Si intermetallic compound powder is subjected to a heat treatment process, wherein the heat treatment process is performed at a heat treatment temperature of 1000°C and a holding time of 1 hour under vacuum conditions, and the Ti5Si3 intermetallic compound powder is prepared by the heat treatment process.
[0035] The molar ratio of Ti:Si in the Ti5Si3 intermetallic compound powder is 63:37.
[0036] Example 2
[0037] A Ti5Si3 / ZrB2 composite material, comprising the following components by weight:
[0038] 40 parts of Ti5Si3 intermetallic compound powder, with Ti5Si3 intermetallic compound as the strengthening and toughening phase;
[0039] 60 parts of ZrB2 powder, with ZrB2 as the matrix; 10 parts of Al2O3 powder and Y2O3 powder as sintering aids; 10 parts of fine silicon powder as a sintering aid.
[0040] The Ti5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Ti-Si intermetallic compound powder is prepared by ball milling for 80 hours using the mechanical alloying process; the prepared Ti-Si intermetallic compound powder is subjected to a heat treatment process, wherein the heat treatment process is performed at a heat treatment temperature of 1250°C and a holding time of 1 hour under vacuum conditions, and the Ti5Si3 intermetallic compound powder is prepared by the heat treatment process.
[0041] The molar ratio of Ti:Si in the Ti5Si3 intermetallic compound powder is 63:37.
[0042] Example 3
[0043] A Ti5Si3 / ZrB2 composite material, comprising the following components by weight:
[0044] 70 parts of Ti5Si3 intermetallic compound powder, with Ti5Si3 intermetallic compound as the strengthening and toughening phase;
[0045] 30 parts of ZrB2 powder, with ZrB2 as the matrix; 10 parts of Al2O3 powder and Y2O3 powder as sintering aids; 10 parts of fine silicon powder as a sintering aid.
[0046] The Ti5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Ti-Si intermetallic compound powder is prepared by ball milling for 80 hours using the mechanical alloying process; the prepared Ti-Si intermetallic compound powder is subjected to a heat treatment process, wherein the heat treatment process is performed at a heat treatment temperature of 1400°C and a holding time of 1 hour under vacuum conditions, and the Ti5Si3 intermetallic compound powder is prepared by the heat treatment process.
[0047] The molar ratio of Ti:Si in the Ti5Si3 intermetallic compound powder is 63:37.
[0048] Example 4
[0049] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0050] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0051] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0052] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0053] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample with a size of 50 mm×5 mm×6 mm by a pressure molding machine at a pressure of 100 MPa for a holding time of 3 minutes. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1000°C and the holding time is 1 hour; at a vacuum degree of 10 -2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0054] Step 3, mixing 10 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 with 90 parts of ZrB2 powder to obtain a composite powder, adding 3 parts of Al2O3 powder and 7 parts of Y2O3 powder as sintering aids to the composite powder, and adding 10 parts of fine silicon powder as a sintering aid to mix to obtain a mixed powder consisting of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; performing a wet ball milling mixing process on the mixed powder by mechanical ball milling, loading the mixed powder into a ball mill, adding 100 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 10 mm into the ball mill for mechanical ball milling mixing for 24 hours to prepare a slurry; loading the slurry into a glass beaker and then placing it in an oven and drying it at 100°C for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 10 parts;
[0055] Step 4, the Ti5Si3 / ZrB2 composite powder obtained in step 3 is mixed with 10 parts of phenolic resin binder and loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to form a slurry, and the slurry is loaded into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 100 MPa for a holding time of 3 minutes, and the pressing is performed A disc sample with a diameter of 40 mm and a height of about 10 mm is prepared; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 100 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to prepare a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0056] Step 5, the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 is placed in a graphite mold, and the graphite mold is placed in a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1500°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 10℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the sintered block of the Ti5Si3 / ZrB2 composite material. The mass fraction of the Ti5Si3 intermetallic compound in the Ti5Si3 / ZrB2 composite material is 10 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0057] Example 5
[0058] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0059] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0060] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0061] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0062] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and a pressure molding machine is used to press the strip sample at a pressure of 120 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1100°C and the holding time is 1 hour; at a vacuum degree of 10 -2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0063] Step 3: Mix 20 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 with 80 parts of ZrB2 powder to obtain a composite powder, add 4 parts by weight of Al2O3 powder and 6 parts by weight of Y2O3 powder as sintering aids to the composite powder, and add 10 parts of fine silicon powder as a sintering aid to obtain a mixed powder consisting of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; pass the mixed powder through The mixed powder was put into a ball mill jar by a wet ball milling mixing process, and 150 ml of anhydrous ethanol and 35 agate grinding balls with a diameter of 11 mm were added to the ball mill jar for mechanical ball milling mixing for 24 hours to prepare a slurry; the slurry was put into a glass beaker and then put into an oven and dried at 100° C. for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 20 parts;
[0064] Step 4: Mix the Ti5Si3 / ZrB2 composite powder obtained in step 3 with 10 parts of phenolic resin binder and put them into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to make a slurry. The slurry is poured into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 120 MPa for 3 minutes, and the pressing is performed A disc sample with a diameter of 40 mm and a height of about 10 mm is obtained; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 120 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out, and isostatically pressed by the cold isostatic press to form a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0065] Step 5: Place the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1550°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2Pa, the heating rate during the sintering process is 15℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the Ti5Si3 / ZrB2 composite sintered block. The mass fraction of Ti5Si3 intermetallic compound in Ti5Si3 / ZrB2 composite material is 20 parts, and a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0066] Example 6
[0067] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0068] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0069] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0070] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0071] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and a pressure molding machine is used to press the strip sample at a pressure of 140 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1200°C and the holding time is 1 hour; at a vacuum degree of 10 -2Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0072] Step 3: Mix 30 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 with 70 parts of ZrB2 powder to obtain a composite powder, add 5 parts by weight of Al2O3 powder and 5 parts by weight of Y2O3 powder as sintering aids to the composite powder, and add 10 parts by weight of fine silicon powder as a sintering aid to obtain a mixed powder consisting of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; mix The powder is subjected to a wet ball milling mixing process by mechanical ball milling, the mixed powder is put into a ball milling jar, 200 ml of anhydrous ethanol and 40 agate grinding balls with a diameter of 12 mm are added to the ball milling jar for mechanical ball milling mixing for 24 hours to prepare a slurry; the slurry is put into a glass beaker and then placed in an oven and dried at 100° C. for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 30 parts;
[0073] Step 4, the Ti5Si3 / ZrB2 composite powder obtained in step 3 is mixed with 10 parts of phenolic resin binder and loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to form a slurry, and the slurry is loaded into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 140MPa for a holding time of 3 minutes, and the pressing A disc sample with a diameter of 40 mm and a height of about 10 mm is prepared; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 140 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to prepare a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0074] Step 5: Place the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1600°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 20℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the sintered block of the Ti5Si3 / ZrB2 composite material, in which the mass fraction of the Ti5Si3 intermetallic compound in the Ti5Si3 / ZrB2 composite material is 30 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0075] Example 7
[0076] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0077] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0078] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0079] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0080] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and a pressure molding machine is used to press the strip sample at a pressure of 150 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1250°C and the holding time is 1 hour; at a vacuum degree of 10 -2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0081] Step three, mixing 40 parts of the Ti5Si3 intermetallic compound powder prepared in step two with 60 parts of ZrB2 powder to obtain a composite powder, adding 6 parts of Al2O3 powder and 4 parts of Y2O3 powder as sintering aids to the composite powder, and adding 10 parts of fine silicon powder as a sintering aid to mix to obtain a mixed powder composed of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; performing a wet ball milling mixing process on the mixed powder by mechanical ball milling, loading the mixed powder into a ball mill, adding 250 ml of anhydrous ethanol and 45 agate grinding balls with a diameter of 13 mm into the ball mill for mechanical ball milling mixing for 24 hours to prepare a slurry; loading the slurry into a glass beaker and then putting it into an oven and drying it at 100°C for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 40 parts.
[0082] Step 4, the Ti5Si3 / ZrB2 composite powder obtained in step 3 is mixed with 10 parts of phenolic resin binder and loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to form a slurry, and the slurry is loaded into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 150MPa for a holding time of 3 minutes, and the pressing A disc sample with a diameter of 40 mm and a height of about 10 mm is prepared; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 150 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out, and isostatically pressed by the cold isostatic press to prepare a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0083] Step 5: Place the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1650°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 23℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the sintered block of the Ti5Si3 / ZrB2 composite material. The mass fraction of the Ti5Si3 intermetallic compound in the Ti5Si3 / ZrB2 composite material is 40 parts, and a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0084] Example 8
[0085] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0086] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0087] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0088] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0089] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and a pressure molding machine is used to press the strip sample at a pressure of 160 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1300°C and the holding time is 1 hour; at a vacuum degree of 10 -2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0090] Step 3: Mix 50 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 with 50 parts of ZrB2 powder to obtain a composite powder, add 7 parts of Al2O3 powder and 3 parts of Y2O3 powder as sintering aids to the composite powder, and add 10 parts by weight of fine silicon powder as a sintering aid to obtain a mixed powder consisting of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; pass the mixed powder through a machine The mixed powder was put into a ball mill, 300 ml of anhydrous ethanol and 50 agate grinding balls with a diameter of 14 mm were added to the ball mill for mechanical ball milling for 24 hours to prepare a slurry; the slurry was put into a glass beaker and then put into an oven for drying at 100°C for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder was 50 parts;
[0091] Step 4, the Ti5Si3 / ZrB2 composite powder obtained in step 3 is mixed with 10 parts of phenolic resin binder and loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to form a slurry, and the slurry is loaded into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 160MPa for a holding time of 3 minutes, and the pressing A disc sample with a diameter of 40 mm and a height of about 10 mm is prepared; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 160 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to prepare a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0092] Step 5, the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 is placed in a graphite mold, and the graphite mold is placed in a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1700°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2Pa, the heating rate during the sintering process is 25℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the Ti5Si3 / ZrB2 composite sintered block, in which the mass fraction of Ti5Si3 intermetallic compound in the Ti5Si3 / ZrB2 composite material is 50 parts, and a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0093] Example 9
[0094] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0095] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0096] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0097] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0098] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and a pressure molding machine is used to press the strip sample at a pressure of 180 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1350°C and the holding time is 1 hour; at a vacuum degree of 10 -2Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0099] Step 3: Mix 60 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 with 40 parts of ZrB2 powder to obtain a composite powder, add 8 parts of Al2O3 powder and 2 parts of Y2O3 powder as sintering aids to the composite powder, and add 10 parts by weight of fine silicon powder as a sintering aid to obtain a mixed powder consisting of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; pass the mixed powder through a machine The mixed powder was placed in a ball mill, and 350 ml of anhydrous ethanol and 55 agate grinding balls with a diameter of 15 mm were added to the ball mill for mechanical ball milling for 24 hours to prepare a slurry; the slurry was placed in a glass beaker and then placed in an oven for drying at 100°C for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder was 60 parts;
[0100] Step 4, the Ti5Si3 / ZrB2 composite powder obtained in step 3 is mixed with 10 parts of phenolic resin binder and loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to form a slurry, and the slurry is loaded into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 180MPa for a holding time of 3 minutes, and the pressing A disc sample with a diameter of 40 mm and a height of about 10 mm is prepared; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 180 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to prepare a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0101] Step 5: Place the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1750°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 30℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the sintered block of the Ti5Si3 / ZrB2 composite material. The mass fraction of the Ti5Si3 intermetallic compound in the Ti5Si3 / ZrB2 composite material is 60 parts, and a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0102] Example 10
[0103] A hot pressing sintering method of a Ti5Si3 / ZrB2 composite material comprises the following steps, calculated by weight:
[0104] Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are:
[0105] Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;
[0106] Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically:
[0107] The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours. The slurry is mixed by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample with a size of 50 mm×5 mm×6 mm by a pressure molding machine at a pressure of 200 MPa for a holding time of 3 minutes. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1400°C and the holding time is 1 hour; at a vacuum degree of 10 -2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder;
[0108] Step 3, mixing 70 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 with 30 parts of ZrB2 powder to obtain a composite powder, adding 9 parts of Al2O3 powder and 1 part of Y2O3 powder as sintering aids to the composite powder, and adding 10 parts of fine silicon powder as a sintering aid to obtain a mixed powder composed of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; performing a wet ball milling mixing process on the mixed powder by mechanical ball milling, loading the mixed powder into a ball mill, adding 400 ml of anhydrous ethanol and 60 agate grinding balls with a diameter of 16 mm into the ball mill for mechanical ball milling mixing for 24 hours to prepare a slurry; loading the slurry into a glass beaker and then placing it in an oven and drying it at 100°C for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 70 parts;
[0109] Step 4, the Ti5Si3 / ZrB2 composite powder obtained in step 3 is mixed with 10 parts of phenolic resin binder and loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to form a slurry, and the slurry is loaded into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder containing a phenolic resin binder; the mixed powder is loaded into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 200 MPa for a holding time of 3 minutes, and the pressing is performed A disc sample with a diameter of 40 mm and a height of about 10 mm is prepared; the disc sample is put into a latex glove, wrapped with the latex glove, sealed and put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure in the cold isostatic press is 200 MPa and the holding time is 5 minutes, after the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to prepare a dense Ti5Si3 / ZrB2 composite powder preform, and a disc sample with a diameter of 40 mm and a height of 8 mm is obtained; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process;
[0110] Step 5: Place the Ti5Si3 / ZrB2 composite powder preform disc sample prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering process; the vacuum hot pressing sintering process preparation method is as follows: the sintering temperature is 1800°C, the hot pressing pressure is 35MPa, the holding time is 2h, and the hot pressing sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 35℃ / min; after the sintering process is completed, the furnace is cooled to prepare the Ti5Si3 / ZrB2 composite material. Through the hot pressing sintering process, a sintered disc sample with a diameter of 40mm and a height of about 6mm can be obtained, which is the sintered block of the Ti5Si3 / ZrB2 composite material. The mass fraction of the Ti5Si3 intermetallic compound in the Ti5Si3 / ZrB2 composite material is 70 parts, and a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature hot pressing sintering process, and there is no residual phenolic resin in the obtained sintered block.
[0111] In the step three, during the hot pressing sintering process, the Ti5Si3 intermetallic compound particles and the ZrB2 particles are subjected to a hot pressing sintering process to form a dense Ti5Si3 / ZrB2 composite material sintered block. The Ti5Si3 particles and the ZrB2 particles have good wettability and can be well bonded together to form a dense sintered block. Moreover, the higher the content of the Ti5Si3 intermetallic compound, the denser the Ti5Si3 / ZrB2 composite material. The purpose of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and the Y2O3 powder sintering aid react at high temperature to form a liquid phase Y3Al5O 12 , i.e. YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, plays a role in filling pores, increases the relative density of the ceramic composite and improves the mechanical properties of the ceramic composite. The role of adding 10 parts by mass of fine silicon powder sintering aid is that the fine silicon powder sintering aid forms liquid silicon liquid at high temperature during the sintering process, and the formation of liquid silicon liquid promotes the densification of the ceramic composite matrix, plays a role in filling pores, increases the relative density of the ceramic composite and improves the mechanical properties of the ceramic composite. Therefore, a Ti5Si3 / ZrB2 composite block with a high density can be prepared by a hot pressing sintering process. Moreover, since the hot pressing sintering process is carried out at a higher sintering temperature and a higher hot pressing pressure, the grains inside the sintered block remain small, so the Ti5Si3 / ZrB2 composite block prepared by the hot pressing sintering process has higher mechanical properties and a uniform and dense microstructure.
[0112] It can be seen from Examples 4-10 that the hot pressing sintering process used in Examples 4-10 is simple in preparation process, low in cost, high in sintering efficiency, and can achieve rapid prototyping. The hot pressing sintering process is low in cost, simple in preparation process, and can also produce dense composite material blocks. Therefore, the main advantages of the present invention over existing technologies are:
[0113] 1) The present invention adopts a mechanical alloying process combined with a heat treatment process to prepare Ti5Si3 intermetallic compound powder, and mixes the prepared Ti5Si3 intermetallic compound powder with ZrB2 powder, adds 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids, and adds 10 parts by mass of fine silicon powder as a sintering aid, and prepares Ti5Si3 / ZrB2 composite powder by wet ball milling and drying, and prepares Ti5Si3 / ZrB2 composite material block by hot pressing sintering process. The purpose of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12, namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, increases the relative density of the ceramic composite and improves the mechanical properties of the ceramic composite. The role of adding 10 parts by mass of fine silicon powder sintering aid is that the fine silicon powder sintering aid forms liquid silicon liquid at high temperature during the sintering process, and the formation of liquid silicon liquid promotes the densification of the ceramic composite matrix, fills the pores, increases the relative density of the ceramic composite and improves the mechanical properties of the ceramic composite. The hot pressing sintering preparation process has low cost, simple preparation process, high sintering efficiency, can achieve rapid molding sintering, and can also prepare Ti5Si3 / ZrB2 composite block with uniform and dense organizational structure.
[0114] 2) The Ti5Si3 / ZrB2 composite material prepared by hot pressing and sintering has a uniform and dense microstructure and high mechanical properties, and also has the properties of high melting point, high hardness, high elastic modulus and the like of Ti5Si3 intermetallic compounds. The Ti5Si3 / ZrB2 composite material prepared by hot pressing and sintering has a high density and a uniform and dense microstructure. The Ti5Si3 / ZrB2 composite material prepared by hot pressing and sintering has high mechanical properties and high hardness, as well as high wear resistance and good high temperature oxidation resistance. The present invention develops a new preparation process for the low-cost manufacture of Ti5Si3 / ZrB2 composite materials, and the present invention lays a foundation for popularizing and promoting the wide application of Ti5Si3 / ZrB2 composite materials in the engineering field.
[0115] 3) In the preparation process of Ti5Si3 / ZrB2 composite material block, the role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aid is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12, namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, and improves the mechanical properties of the ceramic composite. During the heat treatment of the Ti-Si intermetallic compound powder, 10 parts by mass of phenolic resin binder are added to the Ti-Si intermetallic compound powder to improve the strength and hardness of the strip sample blank after pressure forming, prevent fracture and damage when taking the sample and placing it in the graphite crucible, and ensure the integrity of the sample. The phenolic resin binder decomposes into gas at high temperature and volatilizes, leaving only a small amount of residual carbon. A small amount of residual carbon is mixed in the Ti5Si3 intermetallic compound powder after the heat treatment process, which will not affect the final product. The purpose of adding 10 parts by mass of phenolic resin binder to the Ti5Si3 / ZrB2 composite powder is to improve the strength and hardness of the disc sample preform pressed after pressure forming, prevent the disc sample preform from breaking and being damaged when taking the sample and placing it in the graphite mold, and ensure the integrity of the sample. The phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon. The small amount of residual carbon is mixed in the sample after hot pressing and sintering, and will not affect the final product.
[0116] Figure 1 The present invention discloses an X-ray diffraction spectrum of a Ti5Si3 / ZrB2 composite material block prepared by a hot pressing sintering process according to the method provided by the present invention. Figure 1 The XRD pattern of Ti5Si3 / ZrB2 composite material block prepared by hot pressing sintering process. Figure 1 It can be seen that in the XRD spectrum there are diffraction peaks of Ti5Si3 intermetallic compound phase and ZrB2 ceramic phase. In addition, there is a small amount of Y3Al5O 12 The diffraction peak of the phase is the diffraction peak of the YAG phase. During the sintering process, the Al2O3 powder and the Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12, namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, improve the relative density of the ceramic composite and improve the mechanical properties of the ceramic composite. In the XRD spectrum, there are diffraction peaks of the Ti5Si3 intermetallic compound phase and the ZrB2 ceramic phase, which shows that during the hot pressing sintering process, the Ti5Si3 intermetallic compound and the ZrB2 ceramic do not react to generate other impurity phases, and the Ti5Si3 intermetallic compound and the ZrB2 ceramic have good compatibility, so the Ti5Si3 intermetallic compound and the ZrB2 ceramic can be sintered together by the hot pressing sintering process to form a dense Ti5Si3 / ZrB2 composite material, in which the Ti5Si3 intermetallic compound is a reinforcing and toughening phase, and the ZrB2 ceramic is the matrix. The Ti5Si3 intermetallic compound plays a role in reinforcing and toughening the ZrB2 ceramic, and the Ti5Si3 intermetallic compound can significantly improve the mechanical properties of the ZrB2 ceramic. The Ti5Si3 / ZrB2 composite material has the excellent properties of the Ti5Si3 intermetallic compound and the excellent properties of the ZrB2 ceramic. The present invention develops a new preparation process for the low-cost manufacture of the Ti5Si3 / ZrB2 composite material. The hot pressing and sintering process is used to prepare the Ti5Si3 / ZrB2 composite material, which has high preparation efficiency and low preparation cost. The Ti5Si3 / ZrB2 composite material prepared by the hot pressing and sintering process has a high density and a uniform and dense microstructure. The Ti5Si3 / ZrB2 composite material prepared by the hot pressing and sintering process has high mechanical properties and high hardness, as well as good wear resistance and good high-temperature oxidation resistance. The present invention develops a new preparation process for the low-cost manufacture of the Ti5Si3 / ZrB2 composite material, and the present invention lays a foundation for popularizing and promoting the wide application of the Ti5Si3 / ZrB2 composite material in the engineering field.
Claims
1. A Ti5Si3 / ZrB2 composite material, characterized by: Includes the following components: 10 to 70 parts of Ti5Si3 intermetallic compound powder, with Ti5Si3 intermetallic compound as a strengthening and toughening phase; 30 to 90 parts of ZrB2 powder, with ZrB2 as the matrix; 10 parts of Al2O3 powder and Y2O3 powder as sintering aids; 10 parts of fine silicon powder as sintering aid.
2. A Ti5Si3 / ZrB2 composite material according to claim 1, characterized in that: The Ti5Si3 intermetallic compound is prepared by mechanical alloying and heat treatment process, and the Ti-Si intermetallic compound powder is prepared by ball milling for 80 hours using the mechanical alloying process; the prepared Ti-Si intermetallic compound powder is subjected to a heat treatment process, wherein the heat treatment process is performed at a heat treatment temperature of 1000°C to 1400°C, a holding time of 1 hour, and the heat treatment process is performed under vacuum conditions, and the Ti5Si3 intermetallic compound powder is prepared by the heat treatment process.
3. A Ti5Si3 / ZrB2 composite material according to claim 1, characterized in that: The molar ratio of Ti:Si in the Ti5Si3 intermetallic compound is 63:
37.
4. The hot pressing sintering method of the Ti5Si3 / ZrB2 composite material according to claim 1, characterized in that, by weight, The following steps are involved: Step 1: Prepare Ti-Si intermetallic compound powder by mechanical alloying process. The specific steps are: Ti powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the Ti powder to the Si powder is 63:37, and after fixing the four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ti-Si intermetallic compound powder is prepared; the purity of the Ti powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm; Step 2: subjecting the Ti-Si intermetallic compound powder prepared in step 1 to a heat treatment process, specifically: The Ti-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and the mixture is mixed by mechanical ball milling for 24 hours, and a slurry is prepared by wet ball milling. The slurry is placed in a glass beaker and then placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder. The mixed powder is then placed in a steel mold that can be made into a strip sample, and the strip sample is pressed into a strip sample with a size of 50 mm×5 mm×6 mm by a pressure molding machine at a pressure of 100 MPa to 200 MPa for a holding time of 3 minutes. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1000°C to 1400°C, and the holding time is 1 hour; at a vacuum degree of 10 -2 Pa, a porous and loose Ti5Si3 intermetallic compound powder strip sample is obtained, the Ti5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain Ti5Si3 intermetallic compound powder; Ti5Si3 intermetallic compound powder is prepared by a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, so that no phenolic resin remains in the obtained powder; Step 3: 10 to 70 parts of the Ti5Si3 intermetallic compound powder prepared in step 2 are mixed with 30 to 90 parts of ZrB2 powder to obtain a composite powder, 3 to 9 parts of Al2O3 powder and 1 to 7 parts of Y2O3 powder are added to the composite powder as sintering aids, and 10 parts by weight of fine silicon powder is added as a sintering aid to obtain a mixed powder A composed of Ti5Si3 powder, ZrB2 powder, Al2O3 powder, Y2O3 powder and fine silicon powder; the mixed powder A is passed through a machine The mixed powder A is put into a ball mill, 100 to 400 ml of anhydrous ethanol and 30 to 60 agate grinding balls with a diameter of 10 to 16 mm are added into the ball mill for mechanical ball milling for 24 hours to prepare a slurry; the slurry is put into a glass beaker and then put into an oven for drying at 100° C. for 24 hours to prepare a Ti5Si3 / ZrB2 composite powder; wherein the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 10 to 70 parts; Step 4: Mix the Ti5Si3 / ZrB2 composite powder obtained in step 3 with 10 parts of phenolic resin binder and put them into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to make a slurry. The slurry is put into a glass beaker and then put into an oven and dried at 100°C for 24 hours to obtain a Ti5Si3 / ZrB2 mixed powder B containing a phenolic resin binder; the mixed powder B is put into a steel mold capable of making a disc sample and pressed into a disc sample; the pressing adopts a molding press at a pressure of 100MPa to 200MPa for 3 minutes. The method comprises the following steps: pressing the sample into a disc with a diameter of 40 mm and a height of about 10 mm; putting the disc into a latex glove, wrapping it with the latex glove, sealing it and putting it into a cold isostatic press, wherein the medium in the cold isostatic press is hydraulic oil, and the pressure in the cold isostatic press is 100 MPa to 200 MPa for a holding time of 5 minutes. After the holding time is over, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense Ti5Si3 / ZrB2 composite powder preform, thereby obtaining a disc with a diameter of 40 mm and a height of 8 mm; the density of the Ti5Si3 / ZrB2 composite powder preform can be significantly improved by the cold isostatic pressing process; Step 5: Place the Ti5Si3 / ZrB2 composite powder preform prepared in step 4 into a graphite mold, and place the graphite mold into a vacuum hot pressing sintering furnace for vacuum hot pressing sintering; the vacuum hot pressing sintering process preparation method is: sintering temperature is 1500℃~1800℃, hot pressing pressure is 35MPa, holding time is 2h, vacuum degree is 10 -2 Pa, the heating rate is 10-35℃ / min; after vacuum hot pressing sintering, it is cooled with the furnace to prepare Ti5Si3 / ZrB2 composite material. The Ti5Si3 / ZrB2 composite material obtained by hot pressing sintering process is a sintered disc sample with a diameter of 40mm and a height of 6mm, that is, a sintered block of Ti5Si3 / ZrB2 composite material; the mass fraction of Ti5Si3 intermetallic compound in Ti5Si3 / ZrB2 composite material is 10-70 parts; a small amount of phenolic resin is completely decomposed and volatilized during high temperature hot pressing sintering, and there is no residual phenolic resin in the obtained sintered block.
5. The hot pressing sintering method of the Ti5Si3 / ZrB2 composite material according to claim 4, characterized in that: In the step 1, the average particle size of the Ti-Si intermetallic compound powder prepared by ball milling for 60 hours using a mechanical alloying process is 10 to 15 μm, and the powder particle size is extremely fine. The particle size of the Ti5Si3 intermetallic compound powder obtained after the heat treatment process is still 10 to 15 μm, and the obtained Ti5Si3 intermetallic compound powder has an ordered structure.
6. The hot pressing sintering method of the Ti5Si3 / ZrB2 composite material according to claim 4, characterized in that: In the step three, the particle size of the ZrB2 powder is 3 to 5 μm, and the mass fraction of the Ti5Si3 intermetallic compound powder in the Ti5Si3 / ZrB2 composite powder is 10 to 70 parts.